2001
DOI: 10.1017/s0025315401003381
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Cerapopsis Della Valle (Amphipoda: Isaeidae) from the Atlantic coast of Morocco

Abstract: A new species of Cerapopsis (Cerapopsis takamado) is described from the Atlantic coast of Morocco. The genus Cerapopsis, synonymized with Photis Kröyer for nearly a quarter of a century is re-established and now known to contain two species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Sexual dimorphism in C. alexandri sp. nov. has been observed also in pereopods 3 and 4, similarly to C. takamado (Menioui & Myers 2001); the morphology of the remaining characters, such as pereopods, mouthparts, general appearance and body shape, seems to be the same in males and females; thus, the female of C. alexandri sp. nov. should be easily recognized whenever present.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Sexual dimorphism in C. alexandri sp. nov. has been observed also in pereopods 3 and 4, similarly to C. takamado (Menioui & Myers 2001); the morphology of the remaining characters, such as pereopods, mouthparts, general appearance and body shape, seems to be the same in males and females; thus, the female of C. alexandri sp. nov. should be easily recognized whenever present.…”
Section: Discussionmentioning
confidence: 80%
“…Bellan-Santini et al (1989) reported the species in the infralittoral, on sandy bottoms and among algae and Posidonia oceanica meadows. C. takamado was found in shallow waters (12 m), on sandy bottoms of the coast of Marocco (Menioui & Myers 2001). C. alexandri sp.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations